Zip the Chip: Computer Books for Children. - Mellar, Harvey (TLS. Times Literary Supplement, 1983)
Reviews several computer books for children. "Usborne Guide to Understanding the Micro: How It Works and What It Can Do," by Judy Tatchell and Bill Bennett; "Introduction to Computer Programming: Basic for Beginners," by Brian Reffin Smith; "Microprocessors Today," by Robin Webster.